The uses of Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) in forensic entomology - Rozane Badenhorst; Martin H. Villet (Oxford University Press, 2018)
Chrysomya megacephala (Fabricius, 1794) occurs on every continent and is closely associated with carrion and decaying material in human environments. Its abilities to find dead bodies and carry pathogens give it a prominence in human affairs that may involve prosecution or litigation, and therefore forensic entomologists. The identification, geographical distribution and biology of the species are reviewed to provide a background for approaches that four branches of forensic entomology (urban, stored-product, medico-criminal and environmental) might take to investigations involving this fly.